The Effect of Return on Asset (ROA), Debt to Equity Ratio (DER), Earning per Share (EPS), Total Asset Turnover (TATO) and Exchange Rate on Stock Return of Property and Real Estate Companies at Indonesia Stock Exchange Period 2012-2017 - Fakhri Rana Sausan; Lardin Korawijayanti; Arum Febriyanti Ciptaningtias (Ilomata International Journal of Tax and Accounting, 2020)
This research aims to analyze the effect of Return On Asset (ROA), Debt to Equity Ratio (DER), Earning Per Share (EPS), Total Asset Turnover (TATO) and Exchange Rate on Stock Return of Property and Real Estate Companies at Indonesia Stock Exchange period 2012-2017. The sample of this research is consists of 21 property and real estate companies with 6 years period so a total of sample is 126 samples. Sources data is secondary data. The data analysis method in this research is used Multiple Linear Regression. The result shows that Debt to Equity Ratio (DER), Total Asset Turnover (TATO) and Exchange rate of Rupiah/US Dollar partially has got a significant effect on stock return while Return On Asset (ROA) and Earning Per Share (EPS) partially has got an insignificant effect on stock return, its mean Return On Asset (ROA) and Earning Per Share (EPS) can’t be determinant of stock return to investors who want to invest in the capital market.